BILINGUAL INSTRUCTIONS OF INDONESIAN PRIMARY SCHOOLS IN ENDENESE COMMUNITY - Gratiana Sama; Maksimilianus Doi; Febe Fenny Irawati Wanggai (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
This study aims at determining the first-grade teacher perception of primary school on the use of bilingual instructions and the impact on students’ learning outcomes. This qualitative study used the first-grade teacher who taught reading and writing in first year students at SDK Pu’ubheto, Ende Sub-district of Ende Regency. The data were collected through in-depth interview, observation and documentation.  The interview document data were analyzed descriptively. The result showed that the teacher was successfully implementing bilingual instruction. Finally, the implementation of bilingualism by the teacher affected teacher-student interaction and improved students' reading and writing skill and learning outcomes..